SARS-CoV-2 and Orientia tsutsugamushi co-infection in a young teen, Nepal: Significant burden in limited-resource countries in Asia? - Anup Bastola; Ranjit Sah; Sagar K. Rajbhandari; Runa Jha; Zareena Fathah; Bimal S. Chalise; Bikesh Shrestha; Rajesh K. Shah; Pujan Balla; Richa Nepal; Bipin Adhikari; Ali A. Rabaan; Kuldeep Dhama; Alfonso J. Rodriguez-Morales (Narra Sains Indonesia, 2021)
Scrub typhus is caused by Orientia tsutsugamushi, transmitted through bites of infected chiggers (larval mites). During the coronavirus disease 2019 (COVID-19) pandemic, reports of co-infections with endemic pathogens are increasing around the world. Disease with similar clinical presentation may mask other disease diagnosis and increase the morbidity and mortality of the patients. We report co-infection between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and O. tsutsugamushi in a patient in Nepal presenting with fever, headache, retro-orbital pain, generalized body ache, and knee joints pain with a history of dry cough and dyspnea at night. Since scrub typhus is prevalent and considerate as one of the public health consents in Asian countries and the possible overlapping clinical manifestation with other infections including COVID-19, a further investigation required to determine the burden of SARS-CoV-2 and O. tsutsugamushi co-infection in scrub typhus-endemic countries in Asia.